Quality of Root Canal Filling in Manually and Rotary-Filed Single-Rooted Teeth - Mehmood Ahmed Rana, Syed Abdul Rauf Shah, Azhar Iqbal, Saad Haroon, Mansoor Khan, Saqlain Bin Syed Gilani (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to determine if there was a significant difference in root canal obturation quality between single-rooted teeth produced using a manual approach and those prepared using a rotational method, as determined by intraoral periapical radiographs. Study Design: Randomized control trial Place and Duration: This randomized study was conducted at Bakhtawaramin Medical and Dental College during in the period from April, 2022 to September, 2022. Methods: Total 80 patients of both genders were presented. All the included cases had single rooted teeth. Age, gender, and residence were some of the detailed demographic information that was documented after getting informed written consent. Patients were equally divided in two groups. Group I underwent manual root canal treatment in 40 cases while in group II rotary endodontic preparation. Outcomes among both groups were recorded in terms of quality of root canal filling. SPSS 23.0 was used to analyze all data. Results: There were 45 (56.3%) females and 35 (43.7%) males. Mean age of the patients in group I was 33.3±8.35 years and in group II mean age was 34.9±7.23 years. We did not find any significant difference in root canal filling and homogeneity among both groups. Group II showed a significantly good results of T score as compared to group I with p value <0.005. Conclusion: According to the results of this research, the rotary approach yielded higher quality obturations in terms of taper and overall quality than did the traditional method. Despite this, there was no difference between rotary and manual instrumentation in terms of the radiographic technical quality of the root canal obturation with respect to length and density. Keywords: obturation quality, Root Canal Treatment, Manual technique, Rotary Technique